2020
DOI: 10.3389/fneur.2019.01401
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Chronic Subdural Hematoma Recurrence and Stroke Outcomes While Withholding Antiplatelet and Anticoagulant Agents

Abstract: The aging of the western population and the increased use of oral anticoagulation (OAC) and antiplatelet drugs (APD) will result in a clinical dilemma on how to balance the recurrence risk of chronic subdural hematoma (cSDH) with the risk of withholding blood thinners. Objective: To identify features that predicts recurrence, thromboembolism (TEE), hospital stay and mortality. To identify the optimal window for resuming APD or OAC. Methods: We performed a retrospective multivariate analysis of a prospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
2
4
1
Order By: Relevance
“…In our cohort, 47.5% of patients experienced hematoma resolution by 6 months after burr hole evacuation, of which the median surgery-to-resolution time was 161 days (IQR: 85–367); these metrics are similar to those reported in other recent studies ( 19 , 20 ). These results suggest that a large proportion of CSDH survivors continue to live with residual hematomas for several months or even years.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our cohort, 47.5% of patients experienced hematoma resolution by 6 months after burr hole evacuation, of which the median surgery-to-resolution time was 161 days (IQR: 85–367); these metrics are similar to those reported in other recent studies ( 19 , 20 ). These results suggest that a large proportion of CSDH survivors continue to live with residual hematomas for several months or even years.…”
Section: Discussionsupporting
confidence: 88%
“…Though a direct investigation of correlations between hematoma resolution and long-term outcomes is outside the scope of this present study, we believe that characterizing CSDH resolution rates and their predictors serves an important intermediate step toward that end. In our cohort, 47.5% of patients experienced hematoma resolution by 6 months after burr hole evacuation, of which the median surgery-to-resolution time was 161 days (IQR: 85-367); these metrics are similar to those reported in other recent studies (19,20). These results suggest that a large proportion of CSDH survivors continue to live with residual hematomas for several months or even years.…”
Section: Discussionsupporting
confidence: 88%
“…A similar retrospective study of 596 patients following operative management found a recurrence rate of 22.17%. [ 13 ] This is significantly higher than the 5.88% found in the present study. This can be rationalized by the fact that patients with larger unstable hematomas with significant midline shift are prime candidates for operative management.…”
Section: Discussioncontrasting
confidence: 78%
“…In developing countries, the incidence reaches 0.0074% in the elderly group, accounting for nearly 10% of intracranial hemorrhage [ 4 ]. Moreover, elderly patients have a 10-fold increase in the risk of developing CSDH depending on their anticoagulation status [ 5 ]. Because of the increasing rise towards life expectancy and population aging, higher incidence and diagnostic innovation bring new challenges to our treatments.…”
Section: Introductionmentioning
confidence: 99%